TEACHER’S PREPARATION OF LESSON PLAN AND CONSTRAINTS IN ENGLISH AS A FOREIGN LANGUAGE DURING THE PANDEMIC OUTBREAK IN THE JUNIOR HIGH SCHOOL - Wulandari, Putu Devi Mas; Tantra, Dewa Komang; Santosa, Made Hery (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Teaching English online is considered problematic. The availability of a support system and internet quota is the main obstacle. This has an impact on the low ability of students. The purpose of this study is to analyze the abilities and constraints of teachers in preparing lesson plans and student obstacles in EFL learning through Google Meet during the Covid-19 pandemic. The sample of this research is a seventh-grade EFL teacher and also 60 seventh-grade junior high school students. The design applied is a mixed method. Data collection uses three instruments: a rating scale, teacher constraints, and student constraints in EFL through Google Meet. The study results indicate that in preparing the lesson plans, teachers are less capable and have several obstacles in choosing learning methods or techniques, selecting instruments and evaluation techniques, and selecting learning media. In addition, the results of the study indicate that students do not understand the material in lesson plans 3 and 4 and do not like to use Google Meet in learning English based on lesson plans 1.3 and 4. This is related to the limitations of students about it. This research implies that EFL teachers provide online learning plans and focus on selecting techniques or methods, evaluation processes, and media.